The impact of national standardized literacy and numeracy testing on children and teaching staff in remote Australian Indigenous communities. (April 2019) - Macqueen, Susy; Knoch, Ute; Wigglesworth, Gillian; Nordlinger, Rachel; Singer, Ruth; McNamara, Tim; Brickle, Rhianna
All educational testing is intended to have consequences, which are assumed to be beneficial, but tests may also have unintended, negative consequences (Messick, 1989). The issue is particularly important in the case of large-scale standardized tests, such as Australia's National Assessment Program - Literacy and Numeracy (NAPLAN), the intended benefits of which are increased accountability and improved educational outcomes. The NAPLAN purpose is comparable to that of other state and national 'core skills' testing programs, which evaluate cross-sections of populations in order to compare results between population sub-groupings. Such comparisons underpin 'accountability' in the era of population-level testing. This study investigates the impact of NAPLAN testing on one population grouping that is prominent in the NAPLAN results' comparisons and public reporting: children in remote Indigenous communities. A series of interviews with principals and teachers documents informants' first-hand experiences of the use and effects of NAPLAN in schools. In the views of most participants, the language and content of the test instruments, the nature of the test engagement, and the test washback have negative impacts on students and staff, with little benefit in terms of the usefulness of the test data. The primary issue is the fact that meaningful participation in the tests depends critically on proficiency in Standard Australian English (SAE) as a first language. This study contributes to the broader discussion of how reform-targeted standardized testing for national populations affects sub-groups who are not treated equitably by the test instrument or reporting for accountability purposes. It highlights a conflict between consequential validity and the notion of accountability that drives reform-targeted testing.